Teaching And Learning Design Fundamental Using Multimedia As A Tool - Hj Mokhtar, Mumtaz (2002)
This research will identify how multimedia can be as a tool for teaching and learning art and design fundamental. It reviews the content structure of an Art Fundamental course in book and web-sites and relates the art education content structure with the Malaysian Art Education Curriculum ( MAEC). This covers the Malaysian Art Education syllabus from pre-school level until pre-university level and relates with Discipline-Based of Art Education (DBAE)> It identifies key elements from both books and web-sites together with the (MAEC) and finally suggests how those elements can be organised as a multimedia content.